Applications of chemogenetics in non-human primates. (June 2022) - Raper, Jessica; Galvan, Adriana
Abstract: Due to its low invasiveness and controllability, chemogenetic approaches offer a highly attractive option to modulate neuronal activity in basic research and future clinical applications. Chemogenetics have revolutionized neuroscience research by facilitating manipulations of selective brain circuits. To date, however, the large majority of these studies have been conducted in rodent models, while the wide application of chemogenetics in nonhuman primates (NHPs) is yet to occur. Still, important progress has been achieved in the use of chemogenetics in NHP studies in the last few years. Here we review the studies that have been published using chemogenetics in NHPs and discuss the current limitations of the technique to its more widespread use in NHPs and possible ways to overcome them.